RELATIONSHIP BETWEEN SCHOOL CULTURES AND STUDENT ACADEMIC ACHIEVEMENT IN SECONDARY SCHOOLS IN NAKURU COUNTY, KENYA: A COMPARISON BETWEEN PUBLIC AND PRIVATE SCHOOLS - NGARE, NYANG’AU NELSON (Kabarak University, 2024)
School cultures within public in regard to private institutions and student academic achievement cannot be underestimated. The study was motivated by the discrepancy in academic performance between public and private secondary schools in Nakuru County, Kenya, and aimed to understand why private schools, despite being relatively costly, remain attractive to some people while academic achievement in both types of schools varies significantly. This study investigated the relationship between school cultures and academic achievement in the KCSE examination in secondary schools in Nakuru County, Kenya. The study was guided by the following objectives: To establish the relationship between teaching behaviour, student study behaviour, Student Motivation Strategies, and Students Discipline Management Strategies and academic achievement in secondary schools. This study was guided by the theories of educational productivity and organizational culture. The study adopted the descriptive survey design. The target population comprised all candidates who sat the Kenya Certificate of Secondary Education (KCSE) examination in 2021 and all principals of secondary schools in the County. The study employed an outlier approach and multistage sampling. Students were stratified into two groups: public and private schools. Krejcie and Morgan’s (1970) table determined the sample size for each category. Simple random sampling selected the student proportions. The sample included 2,214 students and 80 school principals. Instruments were adapted, achieving a Cronbach's Alpha above 0.7. Validity was ensured with the assistance of the supervisors. Data analysis in SPSS v27 showed a positive correlation between teaching behaviours and academic achievement in top secondary schools. In high-performing public secondary schools, there was a significant positive correlation (r = 0.737; p = 0.000) between Teaching Behaviours and Student academic achievement, contrasting with low-performing public schools (r = 0.071). In Nakuru County, both public and private secondary schools exhibit moderately strong correlations (r = 0.408, p = 0.001 and r = 0.430, p = 0.000, respectively) between students' study behaviour and academic achievement. Notably, top-performing KCSE public schools show a moderately strong correlation (r = 0.498, p = 0.036) between Student Motivation Strategies and academic achievement, whereas in private schools, it's strong (r = 0.921, p = 0.000). Regarding Students Discipline Management Strategies, top-performing public secondary schools have a moderately positive correlation (r = 0.583, p = 0.011), while in private schools, it's stronger (r = 0.686, p = 0.001), both statistically significant. Recommendations include conducting in-service training for teachers to adopt effective teaching cultures, enforcing disciplinary measures, and investing in motivational cultures. Encouraging learners to utilize effective study cultures is also advised. The study can inform decision making process of educational stakeholders.
Keywords: School Culture; Teaching Cultures; Student Study Cultures; Student Motivation Strategies; Academic Achievement